Homology‐guided mutational analysis reveals the functional requirements for antinociceptive specificity of collapsin response mediator protein 2‐derived peptides. (17th March 2017) - Moutal, Aubin; Li, Wennan; Wang, Yue; Ju, Weina; Luo, Shizhen; Cai, Song; François‐Moutal, Liberty; Perez‐Miller, Samantha; Hu, Jackie; Dustrude, Erik T; Vanderah, Todd W; Gokhale, Vijay; et al.
Abstract : Background and Purpose: N‐type voltage‐gated calcium (Cav 2.2) channels are critical determinants of increased neuronal excitability and neurotransmission accompanying persistent neuropathic pain. Although Cav 2.2 channel antagonists are recommended as first‐line treatment for neuropathic pain, calcium‐current blocking gabapentinoids inadequately alleviate chronic pain symptoms and often exhibit numerous side effects. Collapsin response mediator protein 2 (CRMP2) targets Cav 2.2 channels to the sensory neuron membrane and allosterically modulates their function. A 15‐amino‐acid peptide (CBD3), derived from CRMP2, disrupts the functional protein–protein interaction between CRMP2 and Cav 2.2 channels to inhibit calcium influx, transmitter release and acute, inflammatory and neuropathic pain. Here, we have mapped the minimal domain of CBD3 necessary for its antinociceptive potential. Experimental Approach: Truncated as well as homology‐guided mutant versions of CBD3 were generated and assessed using depolarization‐evoked calcium influx in rat dorsal root ganglion neurons, binding between CRMP2 and Cav 2.2 channels, whole‐cell voltage clamp electrophysiology and behavioural effects in two models of experimental pain: post‐surgical pain and HIV‐induced sensory neuropathy induced by the viral glycoprotein 120. Key Results: The first six amino acids within CBD3 accounted for all in vitro activity and antinociception. Spinal administration of a prototypical peptide (TAT‐CBD3‐L5M) reversed pain behaviours. Homology‐guided mutational analyses of these six amino acids identified at least two residues, Ala1 and Arg4, as being critical for antinociception in two pain models. Conclusions and Implications: These results identify an antinociceptive scaffold core in CBD3 that can be used for development of low MW mimetics of CBD3. Linked Articles: This article is part of a themed section on Recent Advances in Targeting Ion Channels to Treat Chronic Pain. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.12/issuetoc